An HIV-1 capsid binding protein TRIM11 accelerates viral uncoating. Issue 1 (December 2016) - Yuan, Ting; Yao, Weitong; Tokunaga, Kenzo; Yang, Rongge; Sun, Binlian
Abstract Background Several members of the TRIM family have been implicated in antiviral defense. Our previous report showed that human TRIM11 potently inhibited HIV-1 transduction by reducing the viral reverse transcripts. These results prompted us to examine the effect of TRIM11 on HIV-1 uncoating, which is closely related to viral reverse transcription. Results Using a combination of in vitro binding and in situ proximity ligation assay, we showed that TRIM11 could interact with HIV-1 capsid. Overexpression of TRIM11 accelerates HIV-1 uncoating and reduces viral reverse transcription indicated by the fate-of-capsid assay and quantitative PCR respectively. Knockdown of TRIM11 enhanced HIV-1 capsid stability and increased viral reverse transcription. However, the replication of another retrovirus MLV is not affected by TRIM11. Moreover, the reverse transcription of HIV-1 mutant bearing capsid G89V showed insensitivity to restriction by TRIM11, indicating that the viral determinant of restriction by TRIM11 might reside on capsid. Using microtubule dynamics inhibitors, we revealed that microtubule dynamics contributes to TRIM11-mediated HIV-1 capsid premature disassembly and the reduction of reverse transcription levels. Finally, we demonstrated that TRIM11 inhibits HIV-1 transduction and accelerates viral uncoating in HIV-1 permissive THP-1-derived macrophages. Conclusions We identify TRIM11 as a new HIV-1 capsid binding protein. Our data also reveal that TRIM11 restricts HIV-1 reverse transcription by accelerating viral uncoating, and microtubule dynamics is implicated in TRIM11-imposed block to early events of HIV-1 replication.